(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2021)
This study aims to describe the conditions, thoughts, events, facts, characteristics, relationships and phenomena regarding the performance of Health Promoters in Magelang Regency, and then it’s obtained to analyze the strategy for improving performance. This research was conducted from January to March 2019. This study used qualitative descriptive analysis research method. Data collection techniques used in this study were interviews, questionnaires and documentation. Drawing conclusions is carried out during the research process by reducing data, after the data is collected then conclusions are taken, and after complete data, final conclusions are taken. The subjects of this study were 30 Health Promoters in Magelang Regency and the object of this study was individual factors (including: competence, motivation, commitment, achievement desire, teamwork, and proactive) and organizational factors (including compensation, facilities and infrastructure, supervision, reward and punishment). The results showed that the performance of Health Promoters in Magelang Regency was underperforms due to low competence, low motivation, low achievement desires, lack of incentives, inadequate facilities and infrastructure, lack of technical guidance and lack of appreciation. The strategy for improving performance are to carried out through improve the relevant education and training, raising expectation to improve motivation, raising passion for improving achievement, increased incentives, providing modern facilities and infrastructure, increased supervision and technical guidance, giving appreciation by apply the reward and punishment appropriately.